Decreasing Hypothermia-Related Escalation of Care in Newborn Infants Using the BEMPU TempWatch: A Randomised Controlled Trial - Donna Lei; Kenneth Tan; Atul Malhotra (MDPI AG, 2021)
Objective: To determine whether incorporating BEMPU TempWatch into the care of LBW/SGA neonates for continuous temperature monitoring decreases the rate of hypothermia requiring escalation of care. Methods: This was a randomised controlled trial conducted in a tertiary hospital in Melbourne, Australia. Participants were late preterm and term LBW/SGA neonates on the postnatal wards. Neonates were randomly assigned to receive either the BEMPU TempWatch in addition to standard care, or to receive standard care alone for the first 28 days of life. The primary outcome was hypothermia requiring escalation of care during initial hospital stay after birth. Results: Trial was discontinued after planned interim feasibility analysis, due to very low rates of hypothermia requiring escalation of care. In total, 75 neonates were included, with 36 in the intervention (TempWatch) group and 39 in the control group. The rate of hypothermia requiring escalation of care was 2/36 (5.6%) in the TempWatch group and 1/39 (2.6%) in the control group (relative risk (RR) 2.17, 95% CI 0.21 to 22.89). Rates of exclusive breastfeeding at discharge were 22/36 (61.1%) in the TempWatch and 13/39 (33.3%) in the control group (RR 1.83, 95% CI 1.10 to 3.07, p = 0.02). All other secondary outcomes were similar between the groups. Conclusions: Low rates of hypothermia requiring escalation of care in a tertiary, high-income setting meant it was not feasible for studying the effects of the TempWatch for this outcome. TempWatch may have a role in promoting exclusive breastfeeding, and this needs to be explored further.